Quantitative determination of D4-cystine in mice using LC-MS/MS and its application to the assessment of pharmacokinetics and bioavailability - Shuning Li; Zhenyao Lu; Li Jiao; Ran Zhang; Yu Hong; Jiye Aa; Guangji Wang (Elsevier, 2021)
Cystine is the primary source material for the synthesis of glutathione. However, the pharmacokinetics and tissue distribution of cystine are largely unknown. A surrogate analyte D4-cystine was employed to generate calibration curves for the determination of levels of D4-cystine and endogenous cystine in mice by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Validation assessments proved the sensitivity, specificity and reproducibility of the method with a lower limit of quantification (LLOQ) of 5 ng/mL over 5-5000 ng/mL in plasma. The pharmacokinetics of D4-cystine were evaluated after administering injections and oral solutions, both of which minimally impacted endogenous cystine levels. The absolute bioavailability of cystine was 18.6%, 15.1% and 25.6% at doses of 25, 50 and 100 mg/kg, respectively. Intravenously injected D4-cystine resulted in dramatically high plasma levels with reduced levels in the brain and liver. Intragastrically administered D4-cystine resulted in high levels in the plasma and stomach with relatively low levels in the lung, kidney, heart and brain.